2003
DOI: 10.1095/biolreprod.102.012336
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Oocytes and Early Embryos Express Multiple Histone H1 Subtypes1

Abstract: Oocytes and embryos of many species, including mammals, contain a unique linker (H1) histone, termed H1oo in mammals. It is uncertain, however, whether other H1 histones also contribute to the linker histone complement of these cells. Using immunofluorescence and radiolabeling, we have examined whether histone H10, which frequently accumulates in the chromatin of nondividing cells, and the somatic subtypes of H1 are present in mouse oocytes and early embryos. We report that oocytes and embryos contain mRNA enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 36 publications
2
38
0
Order By: Relevance
“…Therefore, in humans this variant appears to be specific to pluripotent cells, although it represents a small percentage of the total H1 content in these cells. Indeed the H1.1 expression is restricted to a few tissues in the adult mouse but has also been detected in mouse oocytes and early embryos, in male germ cells during early stages of spermatogenesis, and in several tissues shortly after birth (36,37). Despite the fact that the occupancy of the H1.1 promoter by pluripotency factors has been described in genome wide approaches (19), we did not detect their presence at the reported site.…”
Section: Discussionmentioning
confidence: 55%
“…Therefore, in humans this variant appears to be specific to pluripotent cells, although it represents a small percentage of the total H1 content in these cells. Indeed the H1.1 expression is restricted to a few tissues in the adult mouse but has also been detected in mouse oocytes and early embryos, in male germ cells during early stages of spermatogenesis, and in several tissues shortly after birth (36,37). Despite the fact that the occupancy of the H1.1 promoter by pluripotency factors has been described in genome wide approaches (19), we did not detect their presence at the reported site.…”
Section: Discussionmentioning
confidence: 55%
“…As far as both pronuclei are concerned, a particular localisation of selected acetylated forms of histones h3 and h2A was detected at the nuclear periphery of one and two-cell stage embryos (39). establishment of regulated gene expression in both pronuclei and blastomeres is also associated to the presence of a particular complement of histone h1 subtypes (15). The dynamics of histone modifications is likely to be controlled at the mRnA processing level as a special category of stem-loop binding proteins (SlBP) protecting transcripts from degradation display abundant accumulation in pronuclei and cytoplasm during the first cell cycle (3).…”
Section: The Pronuclei -20 Years Latermentioning
confidence: 95%
“…We have described the gradual disappearance of somatic H1 following the mitotic stage of oogenesis, and the available evidence supports its nearly complete absence from the oocyte by the time of meiosis arrest. While mRNA encoding for all six of the somatic subtypes of H1 could be detected in GV-stage oocytes of Xenopus, none of their corresponding proteins were found to be present using immunological techniques, with the exception of histone H1 o (Hock et al, 1993;Clarke et al, 1997;Clarke et al, 1998;Fu et al, 2003). It was later shown that injected somatic H1 was not able to localize properly in mouse oocyte chromatin, compared to H1oo .…”
Section: Meiotic Phasementioning
confidence: 99%
“…Following this point, the model systems we have been using to describe oogenesis differ widely from each other. In mouse, and presumably humans, most of the somatic histones make their reappearance following the next mitotic division, during the four-cell stage of embryogenesis (Fu et al, 2003). In Xenopus, however, oocyte-specific histone will remain the predominant linker histone until much later in development, at the mid-blastula transition, or MBT (Dimitrov et al, 1993;Fig.…”
Section: Fertilizationmentioning
confidence: 99%